Stakeholder Readiness in Program Implementation "Beautiful Village" (Love Statistics) in Kebun Geran Village - Wiranti Vikra Ardani; Heni Nopianti; Diyas Widiyarti (Al Qalam: Jurnal Ilmiah Keagamaan dan Kemasyarakatan, 2026)
The Kelurahan Cinta Statistik (Kelurahan Cantik) Program is a development program implemented by the Central Statistics Agency (BPS) to improve literacy and utilization of statistical data at the village level as a basis for data-driven development planning. The success of this program is greatly influenced by stakeholder readiness, particularly in terms of human resources. This study aims to determine stakeholder readiness in implementing the Kelurahan Cinta Statistik Program in Kebun Geran Village. This study used a qualitative approach with descriptive methods. Data collection techniques were conducted through interviews, observation, and documentation. The results indicate that stakeholder readiness in implementing the Kelurahan Cinta Statistik Program in Kebun Geran Village is in the sufficient category. Village heads have a good understanding and play an active role in supporting the program, while statistical agents and village officials have basic knowledge and skills that still need to be improved. Supporting stakeholders demonstrate a positive attitude and participation, but their involvement is still limited. Based on the Diffusion of Innovation Theory, this program is in the early to intermediate adoption stage, requiring strengthening of human resource capacity and infrastructure support for optimal and sustainable program operation.